2018
DOI: 10.5194/angeo-36-91-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of equatorial plasma bubbles observed by TEC map based on ground-based GNSS receivers over South America

Abstract: Abstract. A ground-based network of GNSS receivers has been used to monitor equatorial plasma bubbles (EPBs) by mapping the total electron content (TEC map). The large coverage of the TEC map allowed us to monitor several EPBs simultaneously and get characteristics of the dynamics, extension and longitudinal distributions of the EPBs from the onset time until their disappearance. These characteristics were obtained by using TEC map analysis and the keogram technique. TEC map databases analyzed were for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 50 publications
13
77
0
Order By: Relevance
“…The EPBs occurring around the Eastern Pacific, South America, and Atlantic regions (−120–0°E) can rise to over 700 km. This is consistent with the global distribution of density irregularities in the topside ionosphere (600 km) seen in ROCSAT‐1 ion density observations (Su et al, 2006) and TEC observations (Barros et al, 2018). However, some equinoctial EPBs occurring around 60°E to 120°W only grow up to about 500 km.…”
Section: Observations and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The EPBs occurring around the Eastern Pacific, South America, and Atlantic regions (−120–0°E) can rise to over 700 km. This is consistent with the global distribution of density irregularities in the topside ionosphere (600 km) seen in ROCSAT‐1 ion density observations (Su et al, 2006) and TEC observations (Barros et al, 2018). However, some equinoctial EPBs occurring around 60°E to 120°W only grow up to about 500 km.…”
Section: Observations and Discussionsupporting
confidence: 88%
“…However, the EPBs that occur around 60°E to 120°W can only extend up to about ±25° magnetic latitudes in equinoxes. Barros et al (2018) suggested that the EPBs can extend to higher latitude in the South American region in December solstice depending on the apex height of EPBs and the strength of the PRE. It is reasonable since that the PRE can transport the plasma to higher altitude and latitude, then the altitudinal and latitudinal extent of EPBs would be higher.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…When this occurs, it is called the critical level and, as a result, the gravity waves cannot propagate upward (Vadas, 2007). Barros et al (2018), Figueiredo, Buriti, et al (2017), and Makela et al (2013) reported that the nighttime thermospheric neutral wind magnitude, observed by Fabry-Perot interferometer in the Brazilian northeast, is not greater than 150 m/s. Moreover, Drob et al (2015) updated the Horizontal Wind Model and verified that the diurnal thermospheric neutral wind does not exceed 160 m/s on quiet days.…”
Section: Propagation Directionmentioning
confidence: 99%
“…During quiet times, the prereversal enhancement (PRE) of the zonal electric field is responsible for the enhanced upward E × B drift after sunset, which elevates the ionospheric height and subsequently amplifies the growth rate of R-T The morphological features and spatial/temporal variability of EPBs have been widely investigated via case studies and statistical analysis using different observational methods. Moreover, with the fast-growing and global availability of ground-based Global Navigation Satellite Systems (GNSS) measurements and space-based radio occultation data, the evolution characteristics of EPBs can be monitored continuously on both global or regional scales (Aa et al, 2018;Barros et al, 2018;Buhari et al, 2014Buhari et al, , 2017Cherniak et al, 2014;Katamzi-Joseph et al, 2017;Ma & Maruyama, 2006;Nishioka et al, 2008;Takahashi et al, 2015). The spatial variation of EPBs can be derived from the dark streaks of emission depletion in optical observations from ground-based all-sky imagers (ASIs) or space-based ultraviolet (UV) imaging spectrographs (Comberiate & Paxton, 2010;Hickey et al, 2018;Kelley et al, 2003;Kil et al, 2009;Makela, 2006;Martinis et al, 2015;Otsuka et al, 2002;Shiokawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%